Experimental analysis of integration processes practice in vocational education and training - Kozlovskyi, Yu.; Kozlovska, І.; Dolnikova, L. (Problems of Engineer-Pedagogical Education, 2021)
The analysis of the practice of integrating knowledge into the educational process revealed a divergency in the teaching of fundamental and professional disciplines, the dominance of the subject approach to the content of learning, the discrepancy between objectively available links between concepts and phenomena, and the implementation of these interrelationships in a studying process. It has been found out that the problematic type of knowledge integration is not fully realized and the elective component in general education is insufficient. A considerable amount of knowledge without a specific purpose has been revealed in the content of education. In combination with the minor knowledge it overloads the educational and cognitive processes. The purpose of the study is to analyze the level of integration of students' knowledge into practice, to find out the reasons for the existing weaknesses, to identify the specific integration of the content and forms of training in vocational education institutions and the ways of improvement and development of education in general. The study was conducted within the framework of an ascertaining experiment in vocational education institutions in Lviv for three years. The observation method, questioning, analysis of the content of pedagogical documentation and activity results, pedagogical experiment (natural and laboratory), methods of mathematical statistics and computer data processing were efficiently used. The article substantiates the necessity of knowledge integration into the system of vocational education institutions and its positive impact on the quality of students' knowledge, which is an effective means of solving the problem of high-quality professional education and eliminating a number of difficulties in teaching process such as active introduction of integrative learning and integrating the content of educational material on a scientific basis in the educational process. The results of the ascertaining experiment give grounds to claim that the integration of knowledge of vocational education institutions students does not have sufficient scientific substantiation. In the practice of knowledge integration different, often contradictory approaches are implemented, which violates a number of fundamentally important didactic principles and the knowledge does not meet the criteria for selecting the content of training. The theoretical conclusions regarding the state of knowledge integration of the vocational school students were confirmed by the results of the ascertaining experiment, which allowed to prepare the materials for a formative experiment based on partial empirical hypotheses arising from partial theoretical ones.